Communicative Language Teaching and Its Implementation in Online Learning: The Teachers’ Voice - Pamela Gloriez (Journal of English Language Teaching and Linguistics, 2022)
Communicative Language Teaching has been popular as a pedagogical approach in teaching L2 that may help students gain communicative competence. This research aimed to investigate teachers' perceptions of CLT and its implementation in online learning. This research adopted a survey research design, and 30 teachers were involved as the participants. The participants were from junior high school and senior high school teachers in Tanjungpinang-Bintan and Batam. Two questionnaires were used as the instruments. The findings of this study revealed that teachers had a good understanding of the principle of CLT. But most of the teachers showed a misconception about not teaching grammar in CLT. In addition, the teachers also practiced CLT in online learning, and they believed CLT was appropriate and effective. They were also supported with sufficient platform media and the internet even though the instructional materials were insufficient. It shows that the teachers had positive perceptions towards the practice and implementation of CLT in online learning. The result can be used as a reflection for the government to provide adequate instructional media and teachers' training in CLT that may be beneficial for teaching in online learning.